Five new species of the genus Meganaclia Aurivillius, 1892 (Lepidoptera: Erebidae: Arctiinae: Syntomini) - Ignatev, Nikolai; László, Gyula M.; Paśnik, Anna; Fric, Zděnek Faltýnek; Sulak, Harald; Müller, Günter C. (Zootaxa, 2023)
The Afrotropical genus Meganaclia Aurivillius, 1892 is revised, five new species M. smithi sp. n., M. grehani sp. n., M. josephi sp. n., M. johannae sp. n. and M. gaerberfesti sp. n. are described with a key for identification of species based on male genitalia structures. Habitus and genitalia of all taxa are illustrated and a distribution map is provided.